The effects of motivational interviewing on health promoting behaviors of patients with multiple sclerosis - Alireza Dashti; Hojatollah Yousefi; Jahangir Maghsoudi; Masoud Etemadifar (Wolters Kluwer Medknow Publications, 2016)
Background: Multiple sclerosis (MS) is a chronic degenerative disease of the central nervous system (CNS) that can reduce health promoting behaviors in patients. One method of increasing health promoting behaviors is motivational interviewing that can explore and resolve client ambivalence. Materials and Methods: The present clinical trial was carried out among 60 patients with MS. The participants were selected through convenience sampling, and then, allocated to two groups using Mini Pay software. The intervention group participated in three sessions of motivational interviewing per week (1 session every 2 days, and each session lasting 1 h). A two-part questionnaire consisting of demographic data and the Health Promoting Lifestyle Profile (HPLP) II questionnaire was used for data collection. The collected data were analyzed using statistical tests such as independent t-test, and Mann-Whitney and Chi-square tests. Results: No statistically significant difference was observed between the groups in terms of the demographic variables (P > 0.05). The results also showed no significant difference in the overall score of the health promoting behaviors and its dimensions between the two groups before the intervention (P > 0.05). However, 2 weeks and 1 month after the intervention, there was a significant difference between the groups in terms of the overall score and the scores of dimensions, except the spiritual growth dimension (P > 0.05). Conclusions: The findings of this study showed that motivational interviewing can improve health promoting behaviors in patients with MS. Therefore, this method can be used by nurses to improve health promoting behaviors among these patients.